Pemanfaatan Komputerisasi Untuk Perangkat - Murdani Murdani; Ronda Deli Sianturi; Melda Panjaitan (STMIK Budi Darma, 2020)
The development of information technology today has spread and entered every dimension of aspects of human life. The village with all its governmental attributes is an arena that deals directly with the people. Village government is the center of local political power that is personified through the Village Head and his apparatus. The position of the village government is also very important, given the majority of Indonesia's population lives in the countryside. The Village Head and his apparatus as the executor of the village government should have the ability to manage government administration, especially the village apparatus which is directly under the village head, as is the Village Apparatus whose task is to assist the Village Head in the Administration and Technical Services Administration. The existence of village officials who are also entrusted with administrative tasks occupies a very important position because as the lowest organ of the government, they know all the conditions and problems in their area. Thus, village officials in carrying out their daily tasks, especially those related to the presentation the data and information needed, the more hard work and optimal capabilities are demanded in order to facilitate the implementation of government tasks. The function of government is to serve and protect the community. Keywords: Village, government administration, Development and Technical Administration Services